Avaliação da suplementação com vitamina E, na forma natural ou sintética, em mulheres no pós-parto imediato e sua concentração no colostro - Clemente, Heleni Aires (2013)
The Vitamin E consists of eight chemically homologous forms, designated alpha, beta, gamma and delta tocopherols and tocotrienols. Biologically, the alpha-tocopherol (α-TOH) is the most important. Commercially, are found two types of α-TOH a natural (RRR-alpha-tocopherol) and another synthetic (all-rac-alpha-tocopherol). Both forms are absorbed in the intestine, the liver is a preference in favor of forms 2R, due to transfer protein α-TOH. It has higher affinity to these stereoisomers. Newborns are considered high risk for vitamin E deficiency, mainly premature, these have breast milk as a food source for maintenance of serum α-TOH. Clinical signs such as thrombocytosis, hemolytic anemia, retrolental fibroplasia, intraventricular hemorrhage, bronchopulmonary dysplasia and spinocerebellar degeneration can be found in case of a low intake of α-TOH. Thus, maternal supplementation on postpartum with α-TOH can be an efficient way to increase levels of vitamin E in breast milk and thus the consequently increase the supply of micronutrient for the newborn. However, most studies with vitamin E supplementation have been conducted in animals and little is known about the effect of maternal supplementation in humans, as well as on its efficiency to increase levels of α-TOH in human milk, depending on the shape natural or synthetic. The study included 109 women, divided into three groups: control without supplementation (GC) (n=36), supplemented with natural capsule (GNAT) (n=40) and the synthetic capsule (GSINT) (n=33). Blood samples were collected for determination of maternal nutritional status, and colostrums at initial contact and after 24 hours post-supplementation. Analyses were performed by High Performance Liquid Chromatography. Values of α-TOH in serum below 499.6mg/dL were considered deficient. We used the Kruskal-Wallis test and Tukey test to confirm the increase of alpha-tocopherol in milk and efficiency of administered capsules. Daily consumption of α-TOH was based on daily intake of 500 mL of colostrum by the newborn and compared with the nutritional requirement for children from 0 to 6 months of age, 4 mg / day. The mothers had mean concentration of serum α-TOH in 1016 ± 52, 1236 ± 51 and 1083 ± 61 mg / dL, in CG, GNAT and GSINT respectively. There were no women with deficiiency. The GC did not change the concentrations of α-TOH in colostrum. While women supplemented with natural and synthetic forms increased concentrations of α-TOH colostrum in 57.6% and 39%, respectively. By comparing supplemented groups, it was observed a significant difference (p=0.04), the natural capsule more efficient than the synthetic, approximately 49.6%. Individually, 21.1% of the women provided below 4mg/day of α-TOH, after supplementation for this index declined4.1%. Thus, maternal supplementation postpartum raised the levels of alpha-tocopherol in colostrum, and increased efficiency was observed with the natural form